Content Guidance in Formal Problem Solving Processes - Batens, Diderik (Abduction and the Process of Scientific Discovery, 2007)
In this paper, a formal framework to problem-solving processes is presented. The framework is not complete. Nevertheless, even its present sophistication allows one to see that it is promising.\par The framework demonstrably allows one to understand scientific change as content-guided. It will be argued that a formal framework is required in order to make definite and precise statements about the content-guided aspects of scientific problem solving.